1931-1933 Wis. Sess. Laws 778, ch. 359, § 1 - (:unkn) unknown (My University, 1933)
Prohibited selling, possessing, using, or transporting a machine gun, automatic firearm, bomb, hand grenade, projectile, shell, or other container that can contain tear or other gas. Punishable by imprisonment for 1-3 years.
Keywords: MACHINE GUN RESTRICTION; TRANSFER, MANUFACTURE & POSSESSION